Empathizing With Cabetican: Elevating Flood Management Through Design Thinking - Patria Hena P Lagason; Janine T Panlilio; Elisa Faye I Baldevarona; Marie Joyce P Catalan; Maria Margarita R Lavides; Rosanne Marie G Echivarre (Khazanah Sosial, 2025)
This study examines potential mitigation strategies that effectively address flooding issues during typhoons and heavy monsoon rainfall in Barangay Cabetican, Bacolor, Pampanga, Philippines. The authors collected initial data via extensive interviews with six key informants from the community, who expressed their perceptions of flooding, its effects on residents, and descriptions of existing mitigation efforts. The responses revealed that nature, systems, and people’s behaviors, specifically in waste management, are the primary factors influencing flood control. Employing a design thinking approach, practical, community-driven solutions were developed that align with the United Nations’ 11th Sustainable Development Goal of promoting sustainable practices to strengthen the community’s socio-economic resilience.  A community app and a rewards card were among the proposed solutions to promote proactive barangay efforts towards waste and flood management. The authors recommend actions toward cooperation between the local government unit and the community in addressing proactive measures related to disaster preparedness and flooding alleviation.